Father in process of care for children in rural families: health care - Bartosiak Lukash (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article constitutes a part of research project entitled «Paternal attitudes in the rural environment». The research presented in this article, based on qualitative methodology, was conducted in nineteen randomly chosen villages of Plock district. 37 respondents participated in it. The purpose was to determine paternal attitudes in a rural environment. The research does not meet the characteristics of representativeness. The collected research material deepens the scientific knowledge of the essence of a given phenomenon rather than its social scope. The data obtained during the analysis were compiled for a number of concepts that scientifically explain the correctness of the behavior and functioning of a man as a father and his attitudes. The social-scientific personality theory of J. Rotter, U. Bronfenbrenner's human ecology theory, the socio-cognitive theory of A. Bandury and the most important theoretical reference to the problem - «Cognitive concept of attitudes» by D. Crech, R.S. Crutchfield, E.L. Ballachey were taken into consideration. The study covered many issues. According to methodological assumptions, the selection of the sample was deliberately - random. This article is devoted to a small fragment about the father in the childcare process. In accordance with the accepted assumptions, childcare is one of the components of the father's role in the process of parenting. The actions that are linked to organizing the everyday life conditions may be classified as criteria that allow to determine the participation of fathers in childcare processes. The qualitative analysis of collected research material, which is preceded by a theoretical introduction, demonstrates current knowledge on performing first childcare actions, the father's contribution to the child's healthcare, preparing meals, and other.